Antibodies against carbamylated proteins are present in primary Sjögren's syndrome and are associated with disease severity. Issue 8 (8th September 2015) - Bergum, Brith; Koro, Catalin; Delaleu, Nicolas; Solheim, Magne; Hellvard, Annelie; Binder, Veronika; Jonsson, Roland; Valim, Valeria; Hammenfors, Daniel S; Jonsson, Malin V; Mydel, Piotr
Abstract : Objectives: Herein, we investigate the presence and prognostic value of autoantibodies against carbamylated proteins (anti-CarP) in the serum of patients with primary Sjögren's syndrome (pSS). Patients and methods: Serum levels of anti-CarP antibodies were measured in Norwegian patients with pSS (n=78) and corresponding controls (n=74) using ELISA and analysed in relation with exocrine gland function, degree of salivary gland inflammation, signs of ectopic germinal centre (GC) formation and immunological markers. For univariate comparisons, the Mann–Whitney U test and χ 2 or Fisher's exact tests were used. Correlations were assessed with Spearman's rank testing. Multivariate regression analyses were used to assess the effect of anti-CarP positivity on clinical manifestations. Results: Of the patients with pSS, 27% were positive for anti-CarP IgG antibodies. Levels of anti-CarP correlated positively with total IgG, IgM, rheumatoid factor and β2-microglobulin. Importantly, after adjusting for confounding factors, patients positive for anti-CarP had significantly higher focus score. Furthermore, positive anti-CarP status coincided with 9.2-fold higher odds of having developed GC-like structures in the minor salivary glands. As a patient group considered having worse disease outcome, individuals with ectopic GC-like structures also presented with significantly higher levels of anti-CarP antibodies. Conclusions: Presence of anti-CarP in patients with pSS is strongly associated with increased focal lymphocytic infiltration, formation of ectopic GC-like structures in minor salivary glands, and diminished salivary gland function. Even taking into consideration our relatively small cohort we believe that anti-CarP antibodies offer new possibilities for identifying patients with more active disease and at risk of developing additional comorbidity.